Lifestyle intervention during pregnancy in patients with gestational diabetes mellitus and the risk of neonatal hypoglycemia: A systematic review and meta-analysis - Wang, Ya-Hai; Zhou, Huan-Huan; Nie, Zhibin; Tan, Jingwang; Yang, Zicheng; Zou, Shengliang; Zhang, Zheng; Zou, Yu (Frontiers in Nutrition, 2022)
Objective: Neonatal hypoglycemia is a severe adverse consequence of infants born to mothers with gestational diabetes mellitus (GDM), which can lead to neonatal mortality, permanent neurological consequences and epilepsy. This systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to explore the effect of lifestyle intervention during pregnancy in women with GDM on the risk of neonatal hypoglycemia. Methods: PubMed, Web of Science, Cochrane Library, CINAHL and SPORTDiscus databases were searched by April 1st, 2022. Data were pooled as the risk ratio (RR) with 95% confidence intervals (CIs) of the neonatal hypoglycemia. Random-effects, subgroup analyses, meta-regression analysis and leave-one-out analysis were conducted, involving 18 RCTs. Results: Prenatal lifestyle intervention could significantly reduce the risk of neonatal hypoglycemia (RR: 0.73, 95% CI: 0.54 to 0.98, P = 0.037). Subgroup analysis further demonstrated that the reduced risk of neonatal hypoglycemia was observed only when subjects were younger than 30 years, initiated before the third trimester. Meta-regression analysis revealed that maternal fasting glucose levels at trial entry were positively associated with the risk ratio of neonatal hypoglycemia post lifestyle intervention. Conclusion: We found that prenatal lifestyle intervention in GDM women significantly reduced the risk of neonatal hypoglycemia. Only Lifestyle intervention before the third trimester of pregnancy could effectively reduce the risk of neonatal hypoglycemia. Future studies are required to explore the best pattern of lifestyle intervention, and to determine the proper diagnostic criteria of GDM in the first/second trimester of pregnancy.